A community-based transcriptomics classification and nomenclature of neocortical cell types - Yuste, Rafael; Hawrylycz, Michael; Aalling, Nadia; Aguilar-Valles, Argel; Arendt, Detlev; Armañanzas, Ruben; Ascoli, Giorgio A; Bielza, Concha; Bokharaie, Vahid; Bergmann, Tobias Borgtoft; Bystron, Irina; Capogna, Marco; et al. (Nature neuroscience, 2020)
To understand the function of cortical circuits, it is necessary to catalog their cellular diversity. Past attempts to do so using anatomical, physiological or molecular features of cortical cells have not resulted in a unified taxonomy of neuronal or glial cell types, partly due to limited data. Single-cell transcriptomics is enabling, for the first time, systematic high-throughput measurements of cortical cells and generation of datasets that hold the promise of being complete, accurate and permanent. Statistical analyses of these data reveal clusters that often correspond to cell types previously defined by morphological or physiological criteria and that appear conserved across cortical areas and species. To capitalize on these new methods, we propose the adoption of a transcriptome-based taxonomy of cell types for mammalian neocortex. This classification should be hierarchical and use a standardized nomenclature. It should be based on a probabilistic definition of a cell type and incorporate data from different approaches, developmental stages and species. A community-based classification and data aggregation model, such as a knowledge graph, could provide a common foundation for the study of cortical circuits. This community-based classification, nomenclature and data aggregation could serve as an example for cell type atlases in other parts of the body.
Keywords: terminologie jako téma; Cells; neuroglie; Terminology as Topic; Humans; buňky; neokortex; Neocortex; Neuroglia; analýza jednotlivých buněk; Single-Cell Analysis; lidé; zvířata; neurony; výpočetní biologie; Computational Biology; Neurons; transkriptom; Transcriptome; Animals